(untitled) (Carte Romanze, 2025)
The article provides a brief examination of the various occurrences of make-up in troubadour poetry. What emerges is a critical attitude of the troubadours towards cosmetics and the female use of blush and make-up. On the one hand the made-up woman is portrayed as mala dompna, inconstant and frivolous, on the other hand she is the object of a parodic reversal, following a trend that will continue until Italian comic-realist poetry.